If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 5) + -5 = 0 Reorder the terms: 3(5 + 2x) + -5 = 0 (5 * 3 + 2x * 3) + -5 = 0 (15 + 6x) + -5 = 0 Reorder the terms: 15 + -5 + 6x = 0 Combine like terms: 15 + -5 = 10 10 + 6x = 0 Solving 10 + 6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 6x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 6x = 0 + -10 6x = 0 + -10 Combine like terms: 0 + -10 = -10 6x = -10 Divide each side by '6'. x = -1.666666667 Simplifying x = -1.666666667
| 19s-13s-6s+s=19 | | 8.8=m-14.4 | | 7x+2y=94 | | 152+8x=-82-10x | | v^2-5vy-14y^2=0 | | 5r-1=-3(-4+3r)+r | | 2y=7x-94 | | (2s-9)(8s+1)=0 | | 19s-13s-6s=19 | | 3c+2=6c | | 5(m+9)=40+2m+5+3m | | 10x^2=60x+2 | | 4+2(x-8)=8-4x+2 | | -(6x-2y-2)= | | 42s+s^2-s^3=0 | | 6x+9=9x-6 | | 84=12n | | (6t-7)(t+6)=0 | | log(2t+4)=log(13-3t) | | 20+b-b^2=0 | | 11x+4.4=8 | | (6x+1)(x+2)=0 | | x=4(x-1)+1 | | y=2cos(x^2) | | 6x+28=2x+52 | | x^2+6x+8=o | | 5s+s^2+4=0 | | lnx-ln(x+4)=2 | | 5x-5x=-24 | | 4n^2-48n+144=0 | | -(n+3)=-3+3n | | 7x+65=2x+45 |